The effectiveness of therapy for endometriosis-associated pelvic pain resistant to surgical treatment - Mekan R. Orazov; Viktor E. Radzinsky; Roman E. Orekhov (IP Berlin A.V., 2021)
Aim. To assess the efficacy and safety of 24-week therapy with dienogest in patients with endometriosis-associated pelvic pain resistant to surgical treatment. Materials and methods. The study included 126 patients aged 3340 years with external genital endometriosis (EGE) confirmed by laparoscopy and morphological examination (International classification of diseases, 10th revision [ICD-10] N80.1, 80.2, 80.3, 80.4) and with pelvic pain that occurred in 36 months after surgical treatment of EGE (ICD-10 N94.8 "Pain and other conditions associated with female genital organs and menstrual cycle"). The participants were stratified into 3 groups by pain syndrome severity according to the Verbal Analog Scale (VAS). The group-1 included patients with 1040 mm, the group-2 with 4170 mm, and the group-3 with more than 71 mm pain score according to VAS. Patients of all 3 groups were prescribed the denogest (Zafrilla, Gedeon Richter, 2 mg/day) for 24 weeks (according to the current pack insert). Follow-up and assessment of treatment outcomes were carried out over 6 months. Study design: prospective, observational, comparative study. Results. In 3 and 6 months after the start of therapy, there was a stable statistically significant decrease in pain syndrome severity by all scales (Biberoglu Behrman Scale, Numeral Rating Scale, VAS) in each of the groups (p0.01). In all 3 groups, treatment led to an improvement in sexual function, assessed with the Female Sexual Function Index scale, in 3 and 6 months after the start of therapy (p0.01). According to the quality of life in endometriosis (Endometriosis Health Profile) questionnaire, the analyzed indicators significantly improved in all study participants (p0.01). Conclusion. Dienogest is an effective and safe method for the treatment of endometriosis-associated pelvic pain resistant to surgical treatment. Treatment with dienogest for 24 weeks effectively relieves pain, improves symptoms, and improves quality of life and sexual functioning.